RADIOGRAPHIC ALIGNMENT OF CERVICAL SPINE ON A SAMPLE OF ASYMPTOMATIC SUBJECTS - NASREDDINE,MOHAMED AHMED (2017)
ABSTRACT Objective: To present normality parameters for the cervical spine in a sample of the Brazilian population and its distribution by sex and age. Methods: This was a prospective study considering 94 asymptomatic individuals evaluated by panoramic radiograph of the spine for the analysis of the following parameters: cervical lordosis (CL), C2 sagittal vertical axis (SVA-C2), cervical sagittal vertical axis (cSVA), and T1 Slope (TA-T1). The parameter values were compared according to sex and age of individuals. Results: The mean CL was -16.5° (SD: ± 10.8°), SVA-C2 was -3.9 mm (SD: ± 29.2 mm), cSVA was 16.9 mm (SD: ± 10.6 mm) and TA-T1 was 24.8° (SD: ± 7.0°). There was no significant difference between the radiographic parameters when considered with respect to sex and age of individuals (P>0.05). The analysis of correlation among the radiographic parameters showed that the TA-T1 presented the highest correlation with the other parameters, including CL (r= 0.367, P<0.01), SVA-C2 (r= 0.434, P<0.001) and cSVA (r= 0.441, P<0.001). There was also a correlation between SVA-C2 and cSVA (r= 0.32, P= 0.001) and inverse correlation between CL and the cSVA (r= -0.242, P= 0.019). Conclusio: We introduced normality data of the cervical spine alignment in a Brazilian population sample. There was significant correlation among the analyzed parameters, especially considering TA-T1 in relation to the other parameters.